2007
DOI: 10.1007/s10495-007-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

SAHA induces apoptosis in hepatoma cells and synergistically interacts with the proteasome inhibitor Bortezomib

Abstract: Histone deacetylase (HDAC) inhibitors represent a promising group of anticancer agents. This paper shows that the HDAC inhibitor suberoylanilide hydroxamic acid (SAHA) stimulated at 5-10 microM apoptosis in human hepatoma HepG2 and Huh6 cells, but was ineffective in primary human hepatocytes (PHH). In HepG2 cells SAHA induced the extrinsic apoptotic pathway, increasing the expression of both FasL and FasL receptor and causing the activation of caspase-8. Moreover, SAHA enhanced the level of Bim proteins, stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 49 publications
4
75
1
Order By: Relevance
“…10,14 The ability of cells to accumulate higher intracellular concentrations of MTX-PGs correlates with their in vitro and in vivo sensitivity to MTX. 14 This is consistent with the higher IC 50 for MTX in CCRF-CEM (T-ALL) as compared with in NALM6 and other Bp-ALL cells in our study and other reports. 14 The data presented here, demonstrate that upregulation of FPGS mRNA expression by SAHA results in a net pharmacological increase of 30% in intracellular of long-chain MTX-PGs accumulation in ALL cell lines as compared with that in untreated control.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…10,14 The ability of cells to accumulate higher intracellular concentrations of MTX-PGs correlates with their in vitro and in vivo sensitivity to MTX. 14 This is consistent with the higher IC 50 for MTX in CCRF-CEM (T-ALL) as compared with in NALM6 and other Bp-ALL cells in our study and other reports. 14 The data presented here, demonstrate that upregulation of FPGS mRNA expression by SAHA results in a net pharmacological increase of 30% in intracellular of long-chain MTX-PGs accumulation in ALL cell lines as compared with that in untreated control.…”
Section: Discussionsupporting
confidence: 91%
“…[39][40][41] Consequently, SAHA is currently being evaluated in several phase-II studies of patients with hematologic and solid-tumor malignancies. 42 SAHA also has shown synergism in hematological malignancies when combined with a wide variety of agents such as the Src kinase-family inhibitor dasatinib; 43 the heat-shock protein 90 antagonist 17-allylamino-17-demethoxygeldanamycin; 44 the cyclin-dependent kinase inhibitor flavopiridol; 45 the nuclear factor-kB inhibitor Bay 11-7082; 46 the Bcr/Abl TK inhibitors imatinib and MK-0457; 47,48 the MEK1/2 inhibitor PD184352; 49 the proteasome inhibitor bortezomib 50,51 and DNA topoisomerase-II inhibitors, 52 among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of cells throughout the cell cycle phases was ascertained by flow cytometric analysis using a Beckman Coulter Epics XL cytometer as previously reported [19]. In addition, apoptotic cells were detected by flow cytometry using the annexin V-FITC Apoptosis Detection Kit I (BD Biosciences Pharmingen; San Diego, CA), according to the manufacturer's instructions.…”
Section: Cell Cultures Cell Viability and Cell Death Assaymentioning
confidence: 99%
“…HDAC inhibitors are a new class of anticancer drugs, which have shown significant antiproliferative activity against a spectrum of hematological and solid tumors [18,19]. Our previous studies demonstrated the ability of suberoylanilide hydroxamic acid (SAHA), an inhibitor of HDAC, to sensitize human hepatocarcinoma cells to TRAIL-induced apoptosis by enhancing the expression of DR5 and decreasing the level of the anti-apoptotic factor c-FLIP [20].…”
Section: Introductionmentioning
confidence: 99%